SOCIAL BEHAVIOR DISRUPTION AMONG MUSLIM STUDENTS DUE TO THE TIKTOK SYNDROME: A STUDY OF DIGITAL ETHICS IN ISLAMIC EDUCATION - Nury Yahdinil ‘Izzah; Nur Aisyah (Nurul Jadid University, Paiton Probolinggo, East Java, 2025)
This study aims to analyze TikTok syndrome among Muslim students, its ethical relevance, and its implications for Islamic education. TikTok’s expansion has intensified concerns over behavior, communication, and judgment among Muslim youth. In Islamic higher education, excessive use may weaken adab, privacy awareness, and responsibility. This research used a qualitative case study in pesantren-based Islamic higher education. Data were gathered through focus group discussions, observation, and documentation, and analyzed using Miles and Huberman. The findings show that TikTok syndrome causes routine disruption, compulsive use, fragmented interaction, and self-exposure. High use duration was linked to weakened time discipline and reduced control over activities. However, some students limited usage effectively, indicating that disruption is mediated by self-regulation. Islamic digital ethics was found relevant for self-control, verification, and responsible online conduct. Respondents with ethical awareness were more critical toward viral or extreme content. TikTok also had ambivalent implications for Islamic education, supporting learning but disrupting worship consistency and character formation. This study contributes an integrative perspective linking digital disruption, Islamic ethics, and Islamic education objectives. Future research should test Islamic digital literacy interventions in broader settings.